1979
DOI: 10.1073/pnas.76.6.2515
|View full text |Cite
|
Sign up to set email alerts
|

Bedload transport associated with high stream power, Jordan River, Israel

Abstract: During a flood of a magnitude that recurs once in 100 years, boulders up to 1700 mm in size were transported in the Jordan and Meshushim Rivers, northern Israel. Bedload discharge rates were estimated for periods of 3-72 hr of peak flow by a combination of hydrologic and geomorphic methods. Bedload transport rate is proportional to unit stream power in excess of that necessary for initial motion, raised to the power 3/2, as has been shown for data on other rivers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 4 publications
(3 reference statements)
1
9
0
Order By: Relevance
“…The Meshoshim stream ( Fig. 1) drains 160 Km 2 of basaltic terrain in the Golan Heights 7 and is not included within the Jordan River catchment. Nevertheless, the long-term pattern of N ORG in this stream ( Fig.…”
Section: Monitoring Of the Watershedmentioning
confidence: 99%
See 1 more Smart Citation
“…The Meshoshim stream ( Fig. 1) drains 160 Km 2 of basaltic terrain in the Golan Heights 7 and is not included within the Jordan River catchment. Nevertheless, the long-term pattern of N ORG in this stream ( Fig.…”
Section: Monitoring Of the Watershedmentioning
confidence: 99%
“…The Meshoshim stream (Fig. 1) is an example of a small perennial stream (~25 x 10 6 m 3 y -1 ) that drains 160 Km 2 of basaltic terrain in the Golan Heights 7 and flows into the lake from the north-eastern side.…”
Section: Metodsmentioning
confidence: 99%
“…In the Alps, Lenzi et al (2003) also found a bedload component of ∼ 25%, but the size of their study catchment was only 5 km 2 . Other researchers have estimated the bedload flux for rivers more similar to the Marsyandi over single flood events (e.g., Inbar and Schick, 1979), but not averaged over more than a century. Thus, this study is a significant contribution to our knowledge of mountain rivers in glaciated, rapidly eroding ranges.…”
Section: Suspended Load-to-bedload Ratiomentioning
confidence: 99%
“…The palaeo-Amblève can hence be expected to have experienced large peak flows during its periglacial phase despite a limited catchment area, which could be an argument in favour of the hydraulic transport of small boulders. Dislocation of boulders in stream channels or alluvial fans following intense precipitation or rapid ice and snow melting has indeed been reported for various environments and at channel slopes and flow discharges comparable to estimates for the palaeo-Amblève (e.g., Wolman and Eiler, 1958;Boothroyd and Nummedal, 1978;Inbar and Schick, 1979;Carling, 1986).…”
Section: Palaeocompetence In the Boulder Provenance Areamentioning
confidence: 90%